Rancang Bangun Mekantronika Smart Greenhouse Sebagai Budidaya Tanaman Mawar - Tirta Yudistira, Dwi; Arifin, Samsul (Institut Tekonologi dan Binisi Asia Malang, 2024)
Smart Greenhouses are still rarely used by farmers because their development and application are quite complicated. However, besides that, Smart Greenhouse has many advantages in the world of agriculture, namely energy efficiency and working hours of farmers. The methodology used is observation. The observation method is a data collection technique, where the research object makes direct observations of the research object to take a close look at the activities being carried out. The author also conducts an analysis of the needs for materials or components needed to make the tool through several libraries. Mechatronics and spatial systems where this greenhouse work can function properly.